2016
DOI: 10.1080/14620316.2016.1192495
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity andin vitroassessment of salt tolerance responses and associated changes in gene expression of male poplar (Populus) trees

Abstract: In vitro evaluation of salinity effects on male aspen clone W52 (Populus tremula L.) and the hybrid aspen clone T89 (Populus tremula L. × Populus tremuloides 'Michx') were investigated after seawater treatments (control, and 'concentrations' of 8.0, 12.0 and 14.0 dS/m). A salinity level of 14.0 dS/m was found to be lethal. All the vegetative parameters of both Populus clones were significantly decreased at 12.0 dS/m. The amounts of pigments and percentages of K + and Na + , as well as peroxidase activity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Plants increase the production of secondary metabolites, such as silymarin, as a response to both biotic and abiotic stresses. Therefore, one of the strategies to enhance the hepatoprotective compound, silymarin, is by applying abiotic (such as NaCl) or biotic (such as fungal extract or chitosan) elicitors to S. marianum plants [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Plants increase the production of secondary metabolites, such as silymarin, as a response to both biotic and abiotic stresses. Therefore, one of the strategies to enhance the hepatoprotective compound, silymarin, is by applying abiotic (such as NaCl) or biotic (such as fungal extract or chitosan) elicitors to S. marianum plants [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Pitan et al (2011) found that protein, fat, carbohydrate, ash, crude fibre and moisture contents were depleted with increase in mealybug, Rastrococcus invadens William population in mango. According to Khattab and Khattab (2005), the total soluble protein of infested leaves of eucalyptus was lower (1.75±0.61) than those of the healthy ones (2.0±0.89 mg/g) due to feeding by gall-forming psyllid. Miles (1999) found that phloem feeding insects established a sustained interaction with sieve elements (SEs).…”
Section: Total Proteinmentioning
confidence: 95%